2020
DOI: 10.33648/ijoaser.v3i3.78
|View full text |Cite
|
Sign up to set email alerts
|

Students Perceptions in Online Class Learning During the Covid-19 Pandemic

Abstract: The article was to determine student perceptions in online learning. This research was conducted by survey method by giving questionnaires to 239 active students of Bina Bangsa University. Quantitative data were analyzed by descriptive statistics and qualitative data from open-ended questions to gain insight into student perceptions. The analysis shows that 80% of students are willing to take part in online learning, 62% of students claim online learning provides benefits, and 32% of students have difficulty u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 14 publications
1
20
0
6
Order By: Relevance
“…However, researchers (e.g., International Association of Universities & Erasmus Student Network, 2020;Sahu, 2020) have raised issues about the quality of online learning and courses in lieu of students' learning engagement and outcomes, compared to face-to-face ones, as students' perceived online learning success is strongly affected by motivation and engagement (Linjawi & Alfadda, 2018;Sun, 2014;Surani & Hamidah, 2020;Zaveri et al, 2020). During the pandemic, in particular, the researchers (Sahu, 2020;Surani & Hamidah, 2020) have shown keen interest in identifying the level of students' engagement in online learning and ways to improve their online learning engagement because their engagement is a key determinant of their learning outcomes. Students' online learning engagement can be more related to their psychological learning motivation, personal anxiety, and self-learning capability when they are required to take online courses than when they can voluntarily take online courses.…”
Section: Covid-19 and Online Learningmentioning
confidence: 99%
“…However, researchers (e.g., International Association of Universities & Erasmus Student Network, 2020;Sahu, 2020) have raised issues about the quality of online learning and courses in lieu of students' learning engagement and outcomes, compared to face-to-face ones, as students' perceived online learning success is strongly affected by motivation and engagement (Linjawi & Alfadda, 2018;Sun, 2014;Surani & Hamidah, 2020;Zaveri et al, 2020). During the pandemic, in particular, the researchers (Sahu, 2020;Surani & Hamidah, 2020) have shown keen interest in identifying the level of students' engagement in online learning and ways to improve their online learning engagement because their engagement is a key determinant of their learning outcomes. Students' online learning engagement can be more related to their psychological learning motivation, personal anxiety, and self-learning capability when they are required to take online courses than when they can voluntarily take online courses.…”
Section: Covid-19 and Online Learningmentioning
confidence: 99%
“…The phenomenological approach was chosen as a practical method of collecting data, completing the analysis process, and reporting results. Smith and Osborn (2020) suggested that this method was used in many qualitative studies because its phenomenological nature can provide an overview of how to understand a person's experiences or events. That way, the researchers explored what the real purpose of the research being carried out.…”
Section: Methodsmentioning
confidence: 99%
“…Other factors concern the characteristics of the online platforms (Chen, 2017), online learning environment (Cole, Lennon, & Weber, 2019;Damnjanovic et al, 2015;Song et al, 2004), the quality of online teaching resources and materials (Damnjanovic et al, 2015;Horvat et al, 2015;Paechter, Maier, & Macher, 2010;Thurmond, Wamback, Connors, & Frey, 2002;Surani & Hamidah, 2019), as well as the availability of technical support of the platforms (Chen, 2017;Fedynich, Bradley, & Bradley, 2015). These features are all found to have great impacts on students' learning behaviors and motivation in their online learning experiences.…”
Section: Factors Influencing Student Experiences In Online Learningmentioning
confidence: 99%